The arraignment - Martini, Steve, 1946- (Simon & Schuster, Jove Books, 2003)
When a fellow attorney is gunned down, Paul Madriani takes on a client who may have been involved in his friend's murder. Conflicted between his duty to his client and the search for the truth, Madriani sets off on a dangerous quest that takes him from California to the jungles of Mexico and the ancient cultures of the Yucatan.